Pervaporation Of Ethanol/Water Mixture Using Polymeric Membrane - M., Munir; A.H., Qureshi; K., Sanaullah (NCLEAM, 2009)
Pervaportion is the selective evaporation and separation of one component of liquid stream by membrane, which is in direct contact with liquid mixture. This makes pervaporation more energy efficient process. For this study pervaporation apparatus was designed and developed in line with criteria presented in the literature on the subject. Polymeric membrane obtained from Shangai Megavision, China was used in the membrane cell. The membrane unit can also be used for reverse osmosis, gas separation, ultra and nano filteration by simply replacing membrane with other membrane compatible for the selected process. Experiments were performed to separate water from amixture of water/ ethanol. Change in concentration of retentate (feed stream going back to feed tank from membrane cell) with time at different temperatures 60oC, 70oC and 80oC was observed. Moreover effect of temperature on flux was also studied.